Auditor Experience and Audit Quality on Auditor Performance with Professional Ethics as a Moderating Variable in Public Accounting Firms in DKI Jakarta, Surabaya, and Semarang - Zakkiandri; Karsam (International Journal of Science and Society, 2024)
This research identifies and determines the relationship between Auditor Experience, Audit Quality, and Auditor Performance in Public Accounting Firms in DKI Jakarta, Surabaya, and Semarang. Professional Ethics acts as a moderating variable. Quantitative method with a sample of 12 Public Accounting Firms (300 respondents) using purposive sampling. Data analysis uses Multivariate Structural Equation Model (SEM) SmartPLS 3 with a focus on outer model and inner model analysis. The results of this study show that partially, auditor experience has a significant effect on auditor performance (P = 0.000 < 0.05), while audit quality has no significant effect (P = 0.311 > 0.05). Professional ethics as a moderating variable influences audit performance (P = 0.024 < 0.05). However, auditor experience which is moderated by professional ethics, and audit quality which is moderated by professional ethics do not have a significant effect (P = 0.824 and P = 0.242 < 0.05). Simultaneously, auditor performance is influenced by auditor experience and audit quality by 90% (R2 = 0.901).